(untitled) (Environment & Health, 2023)
The relevance of the problem lies in the fact that today’s wartime causes distress in the majority of the population, which affects all systems and structures of the body and leads to psychosomatic disorders. The body’s reaction to prolonged round-the-clock stress is accompanied by the depletion of relevant vitamins and microelements involved in stress adaptation mechanisms, and the accompanying polynutrient deficiency deepens the consequences of distress. The purpose of the work: based on the principles of nutrition of people with increased psycho-emotional stress, to determine the necessary food products and the most important nutrients for alimentary prevention of chronic stress and stress adaptation during martial law. The results. The conducted analysis shows that even in the difficult conditions of wartime, it is possible to reduce anxiety and reduce stress by correcting the diet. To support the body, it will be enough to consume even the simplest, budget products. You should consume protein foods (both animal and vegetable protein) and avoid foods with a high content saturated (solid) fats and sugar, because they only give a small influx of energy, and in the future lead to negative consequences. Conclusions. A diet with a high content of fiber and fresh vegetables is necessary, providing an anti-stress reserve and a resource of vitamins A, C, group B and necessary trace elements. In addition, various cereals, bread, starchy vegetables contain slow carbohydrates, which will help maintain a feeling of satiety. Correcting and minimally diversifying food will help strengthen sleep, calm the nervous system and reduce stress.